Shifting of Research Trends in Fault Detection and Estimation of Location in Power System - Mallinath; Soham Dutta; Jayalakshimi N. S.; Vinay Kumar Jadoun (IEEE Access)
Fault detection is a critical process in ensuring the reliability and safety of modern power systems. With the evolvement of the grid in the modern paradigm, the detection of faults has become complex, particularly due to the incorporation of renewable based distributed generation. Thus, a detailed study of the available fault detection methods needs to be addressed while developing a fault detection model for the modern power system. In line with this, the paper provides a comprehensive overview of different fault detection techniques. The fundamentals of each technique have been elucidated in detail. Moreover, a through comparative analysis of each technique has been done on the basis of several terms to highlight the strengths and shortcomings of each method. Based on the review of these techniques, several prospective research gaps have been identified which will help the researchers to advance the study of power system protection.